PENGARUH DARI TINGKAT SUATU PENDIDIKAN, PEMAHAMAN ILMU AKUNTANSI DAN UKURAN SEBUAH USAHA TERHADAP PENCATATAN PEMBUKUAN SEDERHANA (Studi pada pedagang di Pasar Grosir Setono Kota Pekalongan) - Iis Duwinaeni (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2020)
This research was conducted to find out how the influence of the relationship of the Level of Education, Understanding of Accounting and Business Size to Simple Bookkeeping. In this study took the object of the traders in Wholesale Setono, Pekalongan city. This research is an empirical study, then for data collection using census techniques. The research data was obtained from Wholesalers in Setono Wholesale, Pekalongan city, which is a sample in the study with 50 respondents. Test Analysis in this study uses multiple linear regression analysis. Data analysis was performed using the SPSS program. From the results of tests conducted in this study, it can be concluded that the level of education has a significant effect on simple bookkeeping, then understanding of accounting has a significant effect on simple bookkeeping, while for the size of a business does not have a significant effect on simple bookkeeping. Keywords: Trader, Level of Education, Understanding of Accounting, Size of a Business, Simple Bookkeeping